Crime, Insecurity and Erosion of Democratic Values in Latin America - Pérez, Orlando J. (Revista Latinoamericana de Opinión Pública, 2011)
In the Latin American context of extremely high crime, political scientists and policy makers alike need to ask whether crime, and the associated fear of crime, is helping to build popular support for repressive measures, and by extension, for repressive regimes. In short, is it possible that growing crime is a threat to the durability of democracy in Latin America? To test this proposition, this paper uses the 2008 Americas Barometer surveys. The premise of the paper is that rising crime and insecurity undermine democratic values and increase support for authoritarian measures. As crime rates increase and governments fail to stem the tide, citizen’s belief that democracy is the best system may decline. Some citizens may support the imple- mentation of greater controls or extra-judicial measures. High levels of crime may reduce levels of tolerance and interpersonal trust, thus undermining social capital. Finally, crime victimization and the fear of crime could drive citizens to lose faith in their political institutions, particularly the police and judicial authorities.